Soft Tissue Mobilizations as a Treatment for a Tension-Type Headache - Tamar Gal; Leonid Kalichman (Annals of Musculoskeletal Medicine - Peertechz Publications, 2017)
Background: A tension-type headache (TTH) is the most common form of a headache. The complex interrelation among the various pathophysiological aspects of TTH might explain why this disorder is so difficult to treat. Manual therapy is considered one of the main treatments for TTH. Massage therapy techniques, which act in part to increase blood fl ow to tissue, may reduce the activity of myofascial trigger points. Thus, it is possible that headaches originating from this etiology may be reduced with soft tissue mobilizations. Aim: To perform a review of all available studies with an emphasis on randomized controlled trials to determine whether soft tissue therapy, such as massage and soft tissue inhibition, is a viable treatment for a tension-type headache. Methods: PubMed, Google Scholar, Scopus, and PEDro databases were searched from inception until December 2016 for the following keywords: ''massage'', ''soft tissue therapy'', ''soft tissue mobilization, ''trigger point therapy'', ''a tension-type headache'' or any combination of these words. The reference lists of all articles retrieved were searched as well. PEDro score was used to assess the quality of reviewed studies. Results: A total of eleven studies were included in this review. Seven studies have examined the effect of soft tissue therapy alone with or without comparing to a placebo group and four studies examined this therapy compared to neural and spinal manipulation therapy and to the combination of both treatments. In all studies, soft tissue therapy has provided at least one or more positive effect on TTH patient's outcomes. Conclusions: Soft tissue mobilizations provide better outcomes for patients with TTH than ultrasound therapy or placebo. Headache frequency and intensity and headache disability inventory (HDI) scores can be decreased effectively using this therapy. However, the combination of soft tissue mobilizations with neural manipulation has a larger effect in reducing headache frequency and HDI scores in TTH patients than soft tissue mobilization alone. Therefore, soft tissue mobilization is a viable treatment for a  ensiontype headache, recommended to be combined with manipulation therapy in order to receive a greater therapeutic effect.